Changing Dynamics of Indian Edible Oil Industry - Mittal, Shikha (Journal of Commerce and Trade, 2018)
Till 1990’s the dominant edible oil produced and consumed in India were rapeseed-mustard and groundnut. The technological, economic and policy changes thereafter induced dynamics in consumer demand for food, including edible oils. The possible reason for these shifts are increased urbanization (changing lifestyles), increased awareness, availability of oils in packet form in varied quantities even in remote rural areas, change in relative prices of oils, and increased income levels of households. The results revealed that presently, the dominant edible oil consumed in India is palm oil 50 per cent of the total consumption followed by the soybean and sunflower oil. Rice Bran Oil market in India is still at its nascent stage. In last five years there has been an increase of 20-30 per cent in RBO consumption. The groundnut oil and the mustard/rapeseed oil which was traditionally consumed by households, has been replaced by soybean oil, implying the need for appropriate changes in the production. Classification-JEL : L66, Q13, Q16